A comparative performance evaluation of the reversed Brayton cycle operated heat pump based on thermo-ecological criteria through many and multi objective approaches. (1st March 2019) - Patel, Vivek K.; Raja, Bansi D.
Graphical abstract: Highlights: Thermo-ecological optimization problem of heat pump is developed and investigated. COP, ECOP, exergy efficiency and ecological function are considered as objectives. Comparative analysis between many and multi objective optimization is presented. Relationship of design variables in many/multi objective optimization are obtained. Abstract: Thermodynamic and ecological performance evaluation of the reversed Brayton cycle operated heat pump is analyzed in this work. Performance assessment of the heat pump is carried out through many-objective as well as multi-objective optimization. Maximization of coefficient of performance, ecological coefficient of performance, exergy efficiency and ecological function of the heat pump are considered simultaneously during many-objective optimization. Four operating variable of the heat pump which include temperature ratio, compressor pressure ratio, hot side and cold side heat exchanger effectiveness are investigated in the optimization study. The conflicting level between thermo-ecological behaviour of heat pump is explored through comparison between multi-objective (i.e. two-objective) and many-objective (i.e. four-objective) optimization results. Both, multi-objective and many-objective optimization problem of heat pump are solved using the heat transfer search algorithm and results are presented in the form of Pareto-optimal points. Further, the effect of the design variables and its sensitivity to thermo-ecological behaviour of the heat pump are also presented. Comparative results reveal that, 16.16–37.93% variation in the thermo-ecological behaviour of the heat pump is observed during many-objective optimization as compared to multi-objective optimization. Different decision making approaches are used to select a final optimal solution from Pareto optimal set of many-objective optimization. Finally, the optimization results are compared with the experimental results of the heat pump system. The comparative results revels that 10.95% deviation in co-efficient of performance and 12.3% deviation in exergy efficiency are observed between optimization and experimental results.